Pengaruh Kompetensi Bidang Manufaktur dan Strategi Bisnis terhadap Kinerja Perusahaan Manufaktur di Indonesia - Siti Nursyamsiah (Universitas Islam Indonesia, 2005)
The purpose of this article is threefold. First, a comprehensive measure of production competence/manufacturing competence that assesses the level of support that manufacturing provides for the strategic objectives of a firm is developed. Second, hypotheses relating production competence to several financial measures of business performance are tested using data from a large sample of firms in the manufacturing industry. Third, the impact of business strategy both directly on performance and as a moderating variable in relation to production competence is analyzed. The results of the study suggest that production competence may have more of an effect on business performance for certain strategies than for others.